Społeczny ethos uczonych a procesy "zurzędniczania" nauki = The social ethos of scientists and the processes of science becoming beurocratic - Żukiewicz, Arkadiusz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This article results from the reflection over the social ethos of scientists in the context of the domination of the quantitative perspective on the framing of science. The presented positions concerning the roles assigned to the luminaries of science represent the classical approaches in Polish science. They are mutually complementary, both in the institutional (Prof. K. Twardowski) and social (Prof. F. Znaniecki) contexts. They are also related to the universal message contained in the doctoral vows taken by scientists during the doctoral promotion ceremony, i.e. at the beginning of their academic careers.
Keywords: ethos uczonych; dostojeństwo uniwersytetu; role uczonych; nauki społeczne; nauki humanistyczne; pedagogika społeczna; ethos of scientists; majesty of university; roles of scientists; humanities sciences; social sciences; social pedagogy